Miracle of Silicea Terra in Treating Palmoplantar Dermatitis – A Case Report (Advancements in Homeopathic Research, 2025)
Eczema is one of the most common skin disorders,  where the lesion tends to disseminate, spreading rap idly and distantly from its point of origin. Palmoplan tar dermatitis, an intense, pruritic, relapsing medical  condition requiring long term treatment associated  with dryness, painful fissures and scaling of palm,  sole or both leading to lichenification. Keeping in  mind the several hazardous effects of conventional  treatment where various steroidal ointments and  other calcineurin inhibitors are used, homoeopathy  promises to treat the sick in a rapid, gentle, perma nent way. The presented case report intends to record  individualised homoeopathic constitutional medicine  based on totality of symptoms curing a case of pal moplantar dermatitis with Silicea terra 200 single  dose with no recurrence of symptoms.
Keywords: Eczema; Palmoplantar dermatitis; homoeopathic similimum; Silicea terra